Leadership, Governance and Strategy An Overlooked Connection: Work Design Quality and Leadership Intention - Camgoz, Eyup Ilker; Aycan, Zeynep (ANZAM Conference, 2022)
The present study investigated whether there is a connection between employees’ perceived work design quality and their intention for a possible leadership position at their current organization. The mediating role of worries about leadership and the moderating role of motivation to lead were also examined. The results showed that there is a positive relationship between work design and leadership intention: as employees’ work design quality increases, their intention to be a leader at the current organization increases correspondingly. However, the mediation effect of worries about leadership and the moderation effect of motivation to lead were not significant. Results showed the importance of employee work design for maintaining effective leader candidate pools.